Tumbling-snake model for polymeric liquids subjected to biaxial elongational flows with a focus on planar elongation - Stephanou, Pavlos S.; Kröger, Martin (My University, 2018)
We have recently solved the tumbling-snake model for concentrated polymer solutions and entangled melts in the presence of both steady-state and transient shear and uniaxial elongational flows, supplemented by a variable link tension coefficient. Here, we provide the transient and stationary solutions of the tumbling-snake model under biaxial elongation both analytically, for small and large elongation rates, and via Brownian dynamics simulations, for the case of planar elongational flow over a wide range of rates, times, and the model parameters. We show that both the steady-state and transient first planar viscosity predictions are similar to their uniaxial counterparts, in accord with recent experimental data. The second planar viscosity seems to behave in all aspects similarly to the shear viscosity, if shear rate is replaced by elongation rate.
Keywords: Biaxial flow; Entanglements; Link tension coefficient; Polymer melt; Stochastic differential equation